Far more precious than jewels perspectives on Biblical women - Darr, Katheryn Pfisterer, 1952- (Louisville, KN Westminster, 1991)
Includes bibliographical references and index.
Keywords: Women in the Bible; Bible. O.T. -- biography; Bible and feminism